Alternative Russian-Latin Transliteration (International Journal of Innovative Research in Computer Science & Technology, 2019)
An alternative transliteration of Russian  letters in Latin is proposed, including only four  digraphs, which differs favorably from previous ones  in using all 26 letters of the Latin alphabet (plus an  apostrophe) and in lacking diacritical marks above the  letters and allows the Russian text of any complexity  to be transmitted in Latin letters (and vice versa) with  the maximum simplicity extremely unambiguous.
Keywords: alphabet; transliteration; digraphs; diacritical marks